2019
DOI: 10.4236/ojmm.2019.93012
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection of Biofilm-Producing <i>Staphylococcus aureus</i> Isolates from National Orthopaedic Hospital Dala, Kano State, Nigeria

Abstract: This study evaluated biofilm formation and antibiotic susceptibility in 36 clinical S. aureus isolates recovered from orthopaedic patients and detected the presence of intercellular adhesion and adhesin genes. Staphylococcus aureus was isolated from nasal swab, wound and urine specimens collected from orthopaedic patients in National Orthopaedic Hospital Dala, Kano over a period of three months. The isolates were identified using rapid identification kit for Staphylococcus species. The antibiotics susceptibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
(30 reference statements)
2
3
0
Order By: Relevance
“…The 58% rate of S. aureus isolates exhibiting biofilmforming potential in this present study is more closely related to reports by Torlak and colleagues (46.9%) who studied S. aureus from surfaces in a dental clinic [29], and Khan and colleagues (47.71%) who looked at clinical S. aureus isolates in general [27]. It is also similar to studies carried out in Nigeria which reported a 52.7% and 64% rate of biofilm-forming potential in clinical S. aureus isolates [33,34].…”
Section: Discussionsupporting
confidence: 90%
“…The 58% rate of S. aureus isolates exhibiting biofilmforming potential in this present study is more closely related to reports by Torlak and colleagues (46.9%) who studied S. aureus from surfaces in a dental clinic [29], and Khan and colleagues (47.71%) who looked at clinical S. aureus isolates in general [27]. It is also similar to studies carried out in Nigeria which reported a 52.7% and 64% rate of biofilm-forming potential in clinical S. aureus isolates [33,34].…”
Section: Discussionsupporting
confidence: 90%
“…The biofilm in vitro CRA model used in this study is well established and has been used by several other authors for studying biofilm formation. This finding substantiate CRA method reported prevalence of biofilm forming MRSA 50%, 52.7% and 76.02% [7,11,35] with strong ability of biofilm production seen among the identified strain. Although this study reported low prevalence of biofilm formation, it's worth noting that, phenotypic switch from a free-swimming, planktonic lifestyle to a sessile existence in a biofilm depends on many factors such as environment, availability of nutrients, geographical origin, types of specimen, surface adhesion characteristics and genetic makeup of the organism [36,37].…”
Section: Table 3 Multidrug Resistant (Mdr) Index Of Biofilm-forming M...supporting
confidence: 87%
“…"MRSA is recognized worldwide as an important bacterial pathogen causing mild infections often associated with skin or soft tissue" [4]; however, "it can cause more severe infections such as pneumonia, osteomyelitis, cerebral abscess and sepsis, resulting in high rates of morbidity, high economic burden and possible mortality" [5,6]. "MRSAgenerally has been implicated in bone and wound infections encountered in orthopedic practice" [1,7,8], for example, "osteomyelitis, as well as in postoperative wound infections [9] where they are known to lead to delayed healing of wounds, delayed union, or even nonunion of bones which may lead to the amputation of such bones". "Precisely patients with surgical wounds have been reported to be at high risk of MRSA infection" [10,11] "Compounding the problem even further is the fact that MRSA can form biofilms on biotic and abiotic surfaces" [12].…”
Section: Introductionmentioning
confidence: 99%
“…The medium that was not inoculated was utilized as a control for the determination of the OD of the negative control. The cut-off value (ODc) was calculated by taking the average OD value of the negative control and multiplying it by three times the standard deviation of the negative control (Abdulrahim et al, 2019).…”
Section: Source Of Isolatesmentioning
confidence: 99%
“…The ability of the strains to produce biofilm was divided into four groups based on their OD. These groups are: non-adherent (OD < ODc), weakly adherent (ODc < OD < 2XODc), moderately adherent (2XODc < OD < 4XODc), and strongly adherent (4XODc < OD) (Abdulrahim et al, 2019).…”
Section: Adherence Classificationmentioning
confidence: 99%